Safety Climate and Workers’ Trust in Safety Systems: Key Determinants of Safety Behavior in Construction - Lukman Handoko; Ratih Berliana; Nurul Pujiastuti; Tri Astuti Sugiyatmi; Akhmad Fajri Widodo (Research and Community Service Unit, Poltekkes Kemenkes Kupang, 2026)
This study explores how safety climate in safety systems influences workers' behavior, specifically focusing on safety compliance and participation in high-risk industries like construction. The goal was to examine how safety climate dimensions, such as management safety empowerment and workers' trust in safety systems, affect safety behavior. This study employed a quantitative cross-sectional survey design. A questionnaire was administered to 438 construction workers, and the data were analyzed using descriptive statistics, Pearson's correlation, and multiple regression. The results show significant positive correlations between safety climate dimensions and safety behavior. Management safety empowerment was identified as the most prominent factor associated with both safety compliance and safety participation. In addition, workers’ trust in the effectiveness of safety systems was significantly associated with safety compliance. Age and worker status significantly affected safety perceptions, with older workers and permanent workers demonstrating higher levels of safety compliance and participation. The study found that safety climate factors could explain 21.7% of the variance in safety compliance and 17.0% of the variance in safety participation.